Height-based model for the categorization of athletes in combat sports - Bešlija, T.; Cular, D.; Kezic, A.; Tomljanovic, M.; Ardigò, L. P.; Dhabhi, W.; Padulo, J. (European Journal of Sport Science, 2021)
Reducing bodyweight within a short time participating in kicking combat sports can adversely affect health. This study`s aim creating an improved model to categorize athletes in kicking combat sports. The investigation focused on 795 athletes (11-24 years), participating in the Croatian National Taekwondo Championship. The sample included athletes from both sexes (371 males), cadets (n = 325), juniors (n = 247) and seniors (n = 223). Data were collected during the preparatory period and prior to the athletes competing, using a bioelectrical impedance analysis device. According to current categorization rules, athletes are categorized by arbitrarily determined ranges in bodyweight, whereas, in this current study, the authors have devised an improved model, based on body height and the analysis of data collected. The difference in coefficients between the official model and the proposed, improved categorization method in terms of body height (2.70 and 0.71, respectively), showed that the improved model homogenized athletes almost four times more than the official model, reducing the maximal difference in body height from 29 cm to 9 cm within specific categories. Proposed, improved model had same number of categories as the official structure and directly homogenized differences in height within a category up to a 3-cm maximum for the middle categories and a 9-cm maximum on the periphery of the bands. We expect this improved combat sports categorization model will indirectly reduce differences between other longitudinal body dimensions within categories (thus making match results less predictable) as well as reduce bodyweight manipulation potentially endangering athletes` health.